The role of vitamin D supplementation on levator ani muscle remodeling post-delivery - Rahajeng; Zaen, Taufik Ali (Majalah Obstetri & Ginekologi, 2024)
HIGHLIGHTS 1. In pregnant women, vitamin D insufficiency may plays a role in the development of post-delivery illness.2. Vitamin D supplementation is significant in remodeling of post-delivery levator ani muscle.   ABSTRACT Objectives: Vitamin D is considered a crucial vitamin for the restoration of levator ani muscle strength. Therefore, this study aimed to evaluate the association between vitamin D and levator ani muscle remodeling in the post-delivery period.Materials and Methods: The literature search was conducted across three electronic databases, namely PubMed, Google Scholar, and Springerlink. Our investigation yielded a total of 2613 studies, out of which 8 studies were found to meet the inclusion criteria and were subsequently included in our study. Among these, 4 studies specifically examined the impact of vitamin D micronutrient status on the levator ani/pelvic muscles during the post-delivery period.Results: The mean maximum contraction strength of the levator ani muscles following the administration of vitamin D supplements was 26.77 ± 7.15 cmH2O. The analysis conducted utilizing a paired t-test yielded a p-value of less than 0.05, indicating statistical significance. Additionally, a coefficient correlation of 0.831 was observed, with a p-value also less than 0.05. The findings of this study indicate a noteworthy correlation between levels of vitamin D and the magnitude of levator ani muscle contractions, as evidenced by a statistically significant p-value of less than 0.05.Conclusion: The administration of vitamin D supplements has been found to play a significant role in the remodeling of the levator ani muscle during the post-delivery period. This is evidenced by the observed increase in strength of the levator ani muscles following vitamin D supplementation.